Influência do fortalecimento muscular no equilíbrio e qualidade de vida em indivíduos com doença de Parkinson - Bertoldi, Flavia Cristina; Silva, José Adolfo Menezes Garcia; Faganello-navega, Flávia Roberta [UNESP] (Universidade de São Paulo (USP), 2013)
This study aimed to evaluate the effect of muscle strengthening in the balance, mobility and quality of life (QoL) in individuals with Parkinson's disease (PD), and to check the correlation between muscle strengthening and QoL. Nine subjects belonging to both sexes, diagnosed with PD, participated in this study. Initially, they went through an evaluation of their balance and functional mobility through the Berg Balance Scale (BBS), the Timed Up and Go (TUG) test, and a QoL test through the Parkinson's Disease Questionnaire (PDQ-39). The subjects also performed a test for determining the maximum load (one-repetition maximum) for the muscle groups trained. After the normality and homogeneity of the data were verified, the Student's t-test and Spearman correlation test were carried out. A significance level of p<0.05 was considered. We verified an improvement in balance (p=0.008) and QoL (p=0.013), and a negative correlation between balance and QoL (evaluation: r=-0.65 and p=0.05, revaluation: r=-0.82 and p=0.005). It was concluded that muscle strengthening was efficient in the improvement of balance and QoL in individuals with PD.

Esse estudo teve como objetivo avaliar o efeito do fortalecimento muscular no equilíbrio, mobilidade e na qualidade de vida (QV) de indivíduos com doença de Parkinson (DP), e verificar a correlação entre fortalecimento muscular e qualidade de vida. Participaram do estudo nove sujeitos, de ambos os sexos, com diagnóstico médico de DP. Eles, inicialmente, passaram por avaliação do equilíbrio e da mobilidade funcional por meio da Escala de Equilíbrio de Berg (EEB) e teste Timed Up and Go (TUG) e da QV pelo questionário Parkinson's Disease Questionnaire (PDQ-39). Os sujeitos realizaram ainda o teste de determinação de carga máxima (1 RM) para os grupos musculares treinados. Depois de verificadas a normalidade e homogeneidade dos dados, foram realizados o teste t de Student e o teste de correlação de Spearman. Foi considerado nível de significância de p<0,05. Foi verificada melhora no equilíbrio (p=0,008) e na QV (p=0,013), e correlação negativa entre equilíbrio e QV (avaliação r=-0,65 e p=0,05; e na reavaliação r=-0,82 e p=0,005). O fortalecimento muscular foi eficaz na melhora no equilíbrio e na qualidade de vida de indivíduos com doença de Parkinson.

Este estudio tiene como objetivo evaluar el efecto del fortalecimiento muscular en el equilibrio, movilidad y en la calidad de vida (CV) de individuos con Enfermedad de Parkinson (EP), y verificar la correlación entre el fortalecimiento muscular y calidad de vida. Participaron del estudio nueve sujetos, de ambos sexos, con diagnóstico médico de EP. Inicialmente los sujetos pasaron por una evaluación del equilibrio y la movilidad funcional por medio de la Escala de Equilibrio de Berg (EEB) y el test Timed Up and Go (TUG), y de la CV por el cuestionario Parkinson's Disease Questionnaire (PDQ-39). Los sujetos realizaron también el test de determinación de carga máxima (1 RM) para los grupos musculares entrenados. Después de verificar la normalidad y homogeneidad de los datos fue realizado el Test t de student y el test de correlación de Spearman. Fue considerado nivel de significancia de p<0,05. Fue verificada una mejora en el Equilibrio (p=0,008) y en la CV (p=0,013), y correlación negativa entre el equilibrio y CV (evaluación r= -0,65 y p=0,05; y en la reevaluación r=-0,82 p=0,005). El fortalecimiento muscular fue eficaz en la mejora del equilibrio y en la calidad de vida de individuos con enfermedad de Parkinson.
Influencia del fortalecimiento muscular en el equilibrio y calidad de vida en individuos con enfermedad de Parkinson
Influence of muscle strengthening in the balance and quality of life in individuals with Parkinson's disease
Keywords: doença de Parkinson; qualidade de vida; equilíbrio; Parkinson disease; quality of life; balance